Spectroscopic Analysis of Wheat Fractions and Reconstituted Whole Wheat Mixtures by 1H‐NMR and NIR. Issue 3 (1st November 2016) - Ramakrishnan, Venkatesh; Ridge, Clark D.; Harnly, James; Mazzola, Eugene P.; Luthria, Devanand L.
Abstract : Commercial success of whole wheat products has warranted development of new analytical approaches for differentiating whole grain products from conventional food products made from refined grains. Here, we have analyzed three different wheat fractions (namely, bran, germ, and refined flour) of two wheat varieties. In addition, a whole wheat sample containing all three fractions was also included in the study to investigate the application of two spectral fingerprinting methods—proton nuclear magnetic resonance ( 1 H‐NMR) and near‐infrared (NIR) spectroscopy—for differentiating the three fractions and the whole wheat. Results show that both these methods provide unique spectral fingerprints for the bran, germ, refined, and whole wheat flours. In addition, we were able to distinguish whole grain composed of different ratios of the germ, bran, and refined grain, exemplifying the potential applicability of both fingerprinting methods (NIR and NMR) for the differentiation of whole and refined wheat samples. Principal component analysis on 1 H‐NMR data with four different bin sizes (0.02, 0.04, 0.08, and 0.16 ppm) did not have significant influence on differentiation of the four fractions.